Practice of Business Intelligence System in Nepalese Small and Medium Enterprises - Shiva Prasad Nepal; Shiba Prasad Sapkota (Journal of Balkumari College, 2023)
Everywhere, competition has increased in the digital age. Modern technology makes small business management difficult as well. Customers are aware of the international market. The most recent advancement in management is business intelligence. A data-driven decision to address the challenge encountered by any corporate organization is the current dilemma in management, as opposed to an intuitive or constrained logical decision. Any corporate organization should be concerned with decoding the message from data via scientific analysis. The analysis in this study included 504 Nepalese SEMs. We questioned companies in the manufacturing, service, wholesale, and retail industries on how they used business intelligence in their operations. The survey found that Nepalese SMEs are only just beginning to use business intelligence. For Nepalese businessmen, technological literacy is of the utmost importance. The major worry of Nepalese SMEs is the fear of losing sensitive data.